The status of bladder cancer research worldwide, a bibliometric review and recommendations. Issue 1 (2nd January 2023) - Awada, Hussein; Ali, Adel Hajj; Zeineddine, Mohammad A.; Nassereldine, Hasan; Abdul Sater, Zahy; Mukherji, Deborah
ABSTRACT: Background: Healthcare system costs associated with bladder cancer treatment are among the highest of curable malignancies, and prognosis in advanced disease remains poor. This scoping review examines the worldwide status of bladder cancer research by systematically mapping publications, exploring research topics, support, gaps and limitations that need to be addressed. Methods: We searched the Web of Science database for publications using controlled vocabulary. Results were limited between 2000–2020, and were included in our study based on pre-specified eligibility criteria. Data used for analysis included author's names, country of affiliation, language, journal, citations, and funding. Analysis was conducted using Biblioshiny R and SPSS. Research topics were identified according to sub-filters of title words and strings pre-determined by authors. Results: 40, 657 results were retrieved, of which 19, 976 original articles and reviews met the pre-specified criteria. 92% of the publications originated from 20 countries and were included in the analysis. Trends show an increase across the world, most of which is due to increasing contributions from USA and China. An increase by 1000% in funded publications has been achieved. Studies focused on Surgery, Pathology, and Diagnosis, while Radiotherapy, Palliative care, quality of life and Epidemiology were the least described. Genetics had the most increase while being the most funded. GDP, incidence, prevalence and mortality were each significantly positively correlated with overall bladder cancer research output. Conclusion: This review described the evolution of bladder cancer research. It also identified significant gaps and limitations that need to be highlighted as priority areas for research investment.